ANALISIS KEMAMPUAN AFIKSASI PADA HASIL MENULIS TEKS ULASAN SISWA SMP KELAS VIII - Nurfauziah, Aisyah Sifa; Latifah, Latifah (IKIP Siliwangi, 2019)
This research is motivated by problems often faced by students in the affixation process when writing. The focus of this study is to find answers to the level of students 'abilities in the affixation process with the aim of describing the percentage of students' ability to write the review text. This study uses descriptive quantitative research methods. Data collection techniques in this study used document analysis techniques through the results of writing review texts with instruments in the form of guidelines for constructing affixes. The subjects in this study were class VIII students with a sample of 10, while the object of research was the construction of affixes on the results of writing student review texts. The results of this study indicate that (1) the ability of students in the affixation process on the results of writing review texts to enter in high calcification with a percentage of 82% based on accumulated ability in the use of prefixes, suffixes, and confixes, (2) sequence of affixation process abilities height begins with the affixation process in the form of a suffix with a percentage reaching 100%, followed by a 74% prefix, and ends with a 67% confix, (3) an affixation process that occupies the highest constructional precision, namely suffix -an and -kan, prefix ter- and as well as the confix, to, and the rule, and (4) there is still an affixed form which constructs between the basic form and its infiltration is not appropriate, such as the separation of the basic form with affixes.